2015
DOI: 10.1039/c4ra11489b
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the relationship between structure and photocatalytic properties of TiO2 catalysts

Abstract: Bi-crystalline nanofibres containing 93.2% anatase and 6.8% brookite showed the highest photocatalytic activity among a series of TiO2 photocatalysts because of their ability to generate high photocurrents and to maintain a stable photoresponse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
7
8
0
Order By: Relevance
“…Over the past decades, titania has been widely used in various applications, e.g., in electrochemistry, [1][2][3][4][5] (photo)catalysis, [6][7][8][9][10][11][12][13][14] biomedical processes, [15][16][17][18] development of paints 19,20 and water treatment. [21][22][23] Depending on the synthesis conditions, titania and its composites of various shapes and compositions have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, titania has been widely used in various applications, e.g., in electrochemistry, [1][2][3][4][5] (photo)catalysis, [6][7][8][9][10][11][12][13][14] biomedical processes, [15][16][17][18] development of paints 19,20 and water treatment. [21][22][23] Depending on the synthesis conditions, titania and its composites of various shapes and compositions have been obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In the one-dimensional (1D) morphology, the generation of electron charge carriers is higher along the elongated nanostructures and gives rise to fast transport of charge carriers, due to the hampering of recombination of charge carriers. Hence, 1D nanostructures are gaining more importance for their use in different applications as seen by latest reports [ 9 , 10 ]. For example, Liu et al studied the morphology-dependent photocatalytic properties of bare zinc oxide nanocrystals [ 11 ], which indicated that the rod-shaped ZnO nanostructures have higher photocatalytic activity than the multi-layer disks or truncated hexagonal cones.…”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility is a key property in bioapplications, including delivery of bioactive molecules [6,7], tissue engineering [8], development of biosensors [9], biomimetic [10] and antibacterial materials [11]. Since the discovery of the photoelectric effect in titania [12], enormous effort has been made to develop photocatalytic systems composed of titanium oxide nanostructures or their composites [13][14][15][16][17]. It was also discovered that the shape [18] of the titania particles and the ionic environment [19] influences the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%